Pain and Consolation - López Alonso, Marta (Concilium, 2025)
Consolation and pain open door to contemplation and thought as suffered and lived by human beings during illness. More demanding is how we should be structured, those of us who intend to expose ourselves to pain. He who wants to console must be disposed to remodelling their view, their attention, their care, their responsibility, and their silence. Compassion is always called hyperbole because, while a certain amount of measure and balance are logical in the healthcare field, the rejection of pain can turn us into cold, distant subjects. Comforting in dialogue with science strengthens humanity's stature in the face of pain. In memory of my mother Mercedes.